Compact and modular multicolour fluorescence detector for droplet microfluidics. Issue 13 (7th July 2015) - Cole, Russell H.; de Lange, Niek; Gartner, Zev J.; Abate, Adam R.
<x xml:space="preserve">Abstract</x> We present a compact and modular detection system capable of sub-nanomolar sensitivity utilizing an optical fibre array to encode spectral information recorded by a single photodetector.